Assisted Suicide in Germany: The Landmark Ruling of the German Federal Constitutional Court of February 26, 2020 - Goeken, Hanna; Zwiessler, Franziska (German Law Journal, 2022)
On February 26, 2020, the German Federal Constitutional Court (BVerfG) declared-for the first time in its history-a criminal prohibitory law (strafrechtliche Verbotsnorm) from the German Criminal Code null and void.(1) The provision in question-Section 217 of the German Criminal Code-dealt with the controversial issue of assisted suicide. This case study will briefly examine the previous regulation pertaining to assisted suicide in Germany under Section 217, before scrutinizing its subsequent unconstitutionality as a consequence of the BVerfG's landmark decision. In order to do so, this article will explore the legal background of the decision, the fundamental rights which were held to have been infringed by Section 217, and propose potential ways of regulating assisted suicide in Germany in the future.
CRIS-Team WoS Importer:2022-07-01